Project-based Funding and Novelty in University Research – Findings from Finland and the UK - Antti – Thomas Pelkonen (The Research Institute of the Finnish Economy (ETLA), 2014)
While societal expectations for university research have grown, university research has become more and more dependent on external funding sources. External funding has substantially increased at Finnish – and also UK – universities, and currently in practice a major share of university research is conducted with external funding. This report relates the main findings of a study that analysed the use of project-based research funding instruments at universities, most of which are external. The main focus in the study is on the aspects of novelty and creativity in research and the question of the extent to which different research funding instruments promote these aspects of research. This report draws on different data sources, but mostly on the UNI project (Universities, funding systems, and the renewal of the industrial knowledge base), funded by Tekes innovation research instrument. The major findings include an observation that Finnish research funding system lacks a funder that would strongly encourage risk-taking and novel approaches. Discontinuity and instability of research funding appears as a major challenge for research. There seems to be an overall increase of thematically predefined funding vis-à-vis free researcher-driven funding and close attention should be paid to this balance. Differences between Finland and the UK in terms of novelty generation turned out to be smaller than originally expected.
Keywords: O38; O39; 330; Funding; University research; Novelty; Universitäre Forschung; Forschungsfinanzierung; Finnland; Großbritannien